Indirect tax consultation in project forwarding case study: Petrosains Philharmonic Orchestra Concert Hall tax consultation by Tanjongria Shipping and Forwarding Sdn. Bhd. / Faizal Hamdy Hashim. - Hashim, Faizal Hamdy (1998)
This graduation exercise has been written to provide a clear view and a practical overall understanding of tax exemption application for importation of material or equipment from overseas. In particularly, it covers the process of preparing the tax exemption application, the documentation management, tax implications and advantages of tax exemptions for importer. Current scenario in this operation is the internal working paper and documentation in the operation that cause reduced cost of finished or semi-finished products in the domestic market, in this graduation exercise, the study will focus more on the critical path of tax exemption application. Demand and supply always go together where the customer will make the demand rand the process will continue with supply of goods from the supplies. As for this study, the objective is to find the chance to reduce the cost of the product and at last it will reduce the overall cost of importation or even a project itself.